USING MIND-MAPPING AS A TRANSITION FROM RECEPTIVE TO PRODUCTIVE SKILLS FOR SECOND-DEGREE LEARNERS - Thu, Tran Thanh (VNU Journal of Foreign Studies; Vol 35 No 1DO - 10.25073/2525-2445/vnufs.4344, 2019)
Mindmapping, as a powerful brainstorming tool, is gaining popularity in all fields of science. This article aims at suggesting various activities enclosed with explanations of how this useful utility can be applied for a smooth transition from receptive skills to productive skills while teaching English. As mind maps only date back to 1976, the article initially provides an overview into how to use them and how well they suit the group of grown-up learners. The third part of the article introduces the researcher’s own organization of twelve academic themes throughout the learners’ course. The most important part of the article involves an analysis of various examples of classroom mind maps as they are combined with various activities in classroom settings of various levels throughout the course, highlighting the shifting from one receptive skill to the corresponding productive skill with groups of learners’ contributions to the maps. Last but not least, in the conclusion part, both the summary of the work and some recommendations would be presented about the challenges teachers may encounter and thus should expect during the implementation process.